To solve the equation n + 3(1/2) = 5(1/4) using substitution, we can first simplify the equation:
n + 3/2 = 5/4
Next, we can subtract 3/2 from both sides of the equation to isolate n:
n = 5/4 - 3/2
n = 5/4 - 6/4
n = -1/4
Therefore, n equals -1/4 when you solve the equation using substitution.
Regarding the variable x, since it is not present in the given equation, we cannot determine what x equals.
what does n equal when you solve the equation n + 3( 1)/(2) = 5( 1)/(4) using substitution? What does x equal?
3 answers
what does n equal when you solve the equation n + 3 1/2 = 5 1/4 using substitution?
To solve the equation n + 3 1/2 = 5 1/4 using substitution, we need to convert the mixed numbers to improper fractions first:
3 1/2 = 3 + 1/2 = 3 2/2 = 3 1/2 = 7/2
5 1/4 = 5 + 1/4 = 5 1/4 = 21/4
Now, substitute the improper fractions back into the equation:
n + 7/2 = 21/4
To solve for n, we can first find a common denominator to add the fractions on the right side of the equation:
n + 7/2 = 21/4
n + 7/2 = 10 1/4
n + 7/2 = 10/4 + 1/4
n + 7/2 = 11/4
Next, we can subtract 7/2 from both sides of the equation to isolate n:
n = 11/4 - 7/2
n = 11/4 - 14/4
n = -3/4
Therefore, when you solve the equation n + 3 1/2 = 5 1/4 using substitution, n equals -3/4.
3 1/2 = 3 + 1/2 = 3 2/2 = 3 1/2 = 7/2
5 1/4 = 5 + 1/4 = 5 1/4 = 21/4
Now, substitute the improper fractions back into the equation:
n + 7/2 = 21/4
To solve for n, we can first find a common denominator to add the fractions on the right side of the equation:
n + 7/2 = 21/4
n + 7/2 = 10 1/4
n + 7/2 = 10/4 + 1/4
n + 7/2 = 11/4
Next, we can subtract 7/2 from both sides of the equation to isolate n:
n = 11/4 - 7/2
n = 11/4 - 14/4
n = -3/4
Therefore, when you solve the equation n + 3 1/2 = 5 1/4 using substitution, n equals -3/4.